Long-term low-dose lamotrigine for paroxysmal kinesigenic dyskinesia: a two-year investigation of cognitive function in children - You, Dong-dong; Huang, Yu-mei; Wang, Xiao-yu; Li, Wei; Li, Feng (Frontiers in Psychiatry, 2024)
Objective While low-dose lamotrigine has shown effectiveness in managing paroxysmal kinesigenic dyskinesia (PKD) in pediatric populations, the cognitive consequences of extended use are yet to be fully elucidated. This study seeks to assess the evolution of cognitive functions and the amelioration of attention deficit and hyperactivity disorder (ADHD) symptoms following a two-year lamotrigine treatment in children. Methods This investigation employed an open-label, uncontrolled trial design. Between January 2008 and December 2021, thirty-one participants, ranging in age from 6.5 to 14.1 years, were enrolled upon receiving a new diagnosis of PKD, as defined by the clinical diagnostic criteria set by Bruno in 2004. Comprehensive evaluation of PRRT2 variants and 16p11.2 microdeletion was achieved using whole-exome sequencing (WES) and bioinformatics analysis of copy number variant (CNV) for all subjects. Immediately after diagnosis, participants commenced treatment with low-dose lamotrigine. Cognitive function was assessed using the Wechsler Intelligence Scale for Children-Chinese Revised (WISC-CR) at baseline and after 2 years, with ADHD diagnoses and symptom severity simultaneously assessed by experts in accordance with the DSM-IV diagnostic criteria for ADHD and the ADHD Rating Scale-IV (ADHD-RS-IV). Results Initially, twelve out of 31 patients (38.7%) presented with comorbid ADHD. The latency to treatment initiation was notably longer in PKD patients with ADHD (30.75 ± 12.88 months) than in those without ADHD (11.66 ± 9.08 months), t = 4.856, p<0.001. Notably, patients with a latency exceeding 2 years exhibited a heightened risk for comorbid ADHD (OR = 4.671, P=0.015) in comparison to those with shorter latency. Out of the cohort, twenty-five patients saw the clinical trial to its completion. These individuals demonstrated a marked elevation in WISC-CR scores at the 2-year mark relative to the outset across FSIQ (baseline mean: 108.72 ± 10.45 vs 24 months: 110.56 ± 10.03, p=0.001), VIQ (baseline mean: 109.44 ± 11.15 vs 24 months: 110.80 ± 10.44, p=0.028), and PIQ domains (baseline mean: 106.52 ± 9.74 vs 24 months: 108.24 ± 9.38, p=0.012). Concurrently, a substantial mitigation was observed in ADHD inattention at 2 years compared to baseline (p<0.001), with an average total subscale scores decrement from 9.04 ± 4.99 to 6.24 ± 4.05. Conclusion Prolonged duration of untreated PKD in children may elevate the risk of ADHD comorbidity. Notably, following a 2-year lamotrigine regimen, enhancements were observed in both cognitive test outcomes and ADHD symptomatology.